2022
DOI: 10.1002/lno.12226
|View full text |Cite
|
Sign up to set email alerts
|

Stream metabolism sources a large fraction of carbon dioxide to the atmosphere in two hydrologically contrasting headwater streams

Abstract: Headwater streams are control points for carbon dioxide (CO 2 ) emissions to the atmosphere, with relative contributions to CO 2 emission fluxes from lateral groundwater inputs widely assumed to overwhelm those from in-stream metabolic processes. We analyzed continuous measurements of stream dissolved CO 2 and oxygen (O 2 ) concentrations during spring and early summer in two Mediterranean headwater streams from which we evaluated the contribution of in-stream net ecosystem production (NEP) to CO 2 emission. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…A synthesis of US streams reports an average CO 2 concentration of 5.3 mg L −1 [this study: 2.3; 0.2-7.1] (mean; range shown in brackets throughout section) and flux of 18.9 g m −2 d −1 [this study: 2.9; −0.4 to 10.5] in third order streams (Butman & Raymond, 2011). While the total flux from New Hope Creek is lower, the fraction of CO 2 flux due to in stream metabolism is comparable to that in some streams (Bernal et al, 2022;Rocher-Ros et al, 2020) but higher than is reported in most streams of similar size (Gómez-Gener et al, 2016;Lupon et al, 2019;Rasilo et al, 2017). The fraction we measured is likely a conservative estimate, as we would expect the lowest contribution of instream metabolism during the winter, which is when we collected most of our measurements.…”
Section: Magnitudes and Patternsmentioning
confidence: 67%
See 1 more Smart Citation
“…A synthesis of US streams reports an average CO 2 concentration of 5.3 mg L −1 [this study: 2.3; 0.2-7.1] (mean; range shown in brackets throughout section) and flux of 18.9 g m −2 d −1 [this study: 2.9; −0.4 to 10.5] in third order streams (Butman & Raymond, 2011). While the total flux from New Hope Creek is lower, the fraction of CO 2 flux due to in stream metabolism is comparable to that in some streams (Bernal et al, 2022;Rocher-Ros et al, 2020) but higher than is reported in most streams of similar size (Gómez-Gener et al, 2016;Lupon et al, 2019;Rasilo et al, 2017). The fraction we measured is likely a conservative estimate, as we would expect the lowest contribution of instream metabolism during the winter, which is when we collected most of our measurements.…”
Section: Magnitudes and Patternsmentioning
confidence: 67%
“…It has been widely assumed that aquatic production of greenhouse gases (GHGs) is likely to be important only in large rivers (J. J. Cole & Caraco, 2001; Vannote et al., 1980) due to the higher connectivity of headwaters to terrestrial gas inputs (Hotchkiss et al., 2015) and shorter processing time available for organic carbon in these systems (Catalán et al., 2016). However, recent studies have shown that mineralization of allochthonous organic matter can be a primary source of river GHG fluxes in some headwater streams as well (Bernal et al., 2022; Rocher‐Ros et al., 2020), contributing to the high GHG fluxes observed in headwater streams (Li et al., 2021; Stanley et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of high p CO 2 could result from the lack of C supply from the surrounding landscape. High p CO 2 in small rivers are typically derived from two sources, including groundwater carrying inorganic C originated from soils and in‐stream decomposition of terrestrial organic C (Bernal et al., 2022; Duvert et al., 2018; Marx et al., 2017). In the ERB, groundwater CO 2 input could be substantially diluted due to extensive precipitation in this watershed (B. Liu et al., 2021), implying that in‐stream metabolism could be the key mechanic controlling the p CO 2 dynamics in small rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Since we only measured CO 2 concentrations-not those of other DIC species (but see the efforts of Duvert et al, 2019;Wang et al, 2021)-carbonate buffering changes when lateral inflows mix with river water are unknown. The "other" flux reported in this study, arrived at by mass balance, encompasses all those potential carbonate equilibria, but also fluxes due to anaerobic respiration (Bernal et al, 2022) and methane oxidation (Rasilo et al, 2017). Further work will be needed to fully constrain all the overlapping elements of riverine C cycle.…”
Section: Discussionmentioning
confidence: 97%
“…There are two main pathways—the “reactor” and “chimney”—for terrestrial C to subsidize riverine CO 2 emission, and many recent studies have focused on partitioning the contribution of each (Bernal et al., 2022; Hotchkiss et al., 2015; Lupon et al., 2019; Rasilo et al., 2017; Saccardi & Winnick, 2021). The “reactor” pathway arises from lateral transport of terrestrially derived organic matter, which fuels in‐stream ecosystem respiration (ER), producing net CO 2 in the stream that then off‐gases (Cole & Caraco, 2001; Mayorga et al., 2005).…”
Section: Introductionmentioning
confidence: 99%